Drug war heresies : learning from other vices, times, and places - MacCoun, Robert J. (RAND studies in policy analysis., 2001)
(Publisher-supplied data) This book provides the first multidisciplinary and nonpartisan analysis of how the United States should decide on the legal status of cocaine, heroin and marijuana. It draws on data about the experiences of Western European nations with less punitive drug policies as well as new analyses of America's experience with legal cocaine and heroin a century ago, and of America's efforts to regulate gambling, prostitution, alcohol and cigarettes. It offers projections on the likely consequences of a number of different legalization regimes and shows that the choice about how to regulate drugs involves complicated tradeoffs among goals and conflict among social groups. The book presents a sophisticated discussion of how society should deal with the uncertainty about the consequences of legal change. Finally, it explains, in terms of individual attitudes toward risk, why it is so difficult to accomplish substantial reform of drug policy in America.